Building Occupational Safety and Health (K3): Analysis of the Work Environment and Work Discipline - Saputra, Farhan; M. Rizky Mahaputra (Dinasti Research, 2022)
Literature Review Article Building Occupational Safety and Health (K3): Analysis of the Work Environment and Work Discipline is a scientific article that aims to build a research hypothesis on the influence between variables that will be used in further research, within the scope of Human Resource Management. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are that: 1) the work environment affects Occupational Safety; 2) Work Environment has an effect on Occupational Health; 3) Work Discipline affects Occupational Safety; 4) Work Discipline has an effect on Occupational Health; and 5) Occupational Safety affects Occupational Health.